717 AMG 160, a prostate-specific membrane antigen (PSMA)-targeted BiTE® immuno-oncology therapy, is active in models of advanced prostate cancer that are resistant to radioligand therapy. (9th November 2020) - Lueckerath, Katharina; Bailis, Julie; Current, Kyle; Salvati, Mark; Radu, Caius; Czernin, Johannes
Abstract : Background: AMG 160 is an HLE BiTE ® (half-life extended bispecific T-cell engager) that binds PSMA on prostate cancer cells and CD3 on T-cells and induces redirected T-cell lysis of PSMA-expressing cells. This mechanism may allow the BiTE molecule to be active in settings where other targeted or immune therapies have failed. Here, we evaluated the activity of AMG 160 in mouse models of advanced prostate cancer that are resistant to 177 Lu-PSMA-617, a PSMA-targeted radioligand therapy that has emerged as a promising treatment modality for metastatic castration-resistant prostate cancer (mCRPC). Methods: Two prostate cancer models were tested in 6–8-week-old male NCG mice: one cohort had established subcutaneous C4-2 TP53 -/- tumors (C4-2 cells with TP53 knockout), and the other cohort had established systemic C4-2 TP53 wt/wt tumors that mimic metastatic lesions (intracardiac injection). PSMA levels in both models (~255, 000 PSMA/cell) are sufficient for tumor growth inhibition with 177 Lu-PSMA-617. Mice were administered a single intravenous (IV) infusion of human T-cells. Three days later, mice were treated with 1 cycle of 177 Lu-PSMA-617 (30 MBq, IV), or 3 weekly doses of AMG 160 (1 mg/kg, IV) or of a control HLE BiTE molecule (1 mg/kg, IV; target not expressed on C4-2 cells). Therapeutic efficacy was assessed by tumor burden measurements, time to progression (TTP), and survival. Results: In both prostate cancer models, AMG 160 treatment significantly improved disease control (figure 1). Median TTP was not reached in the AMG 160 group (p<0.0001), whereas it was 31d ( 177 Lu-PSMA-617) and 23.5d (control) in the subcutaneous model, and 68d ( 177 Lu-PSMA-617) and 50.5d (control) in the systemic model. Median survival was not reached in the AMG 160 group (p<0.0001); it was 39d ( 177 Lu-PSMA-617) and 26.5d (control) in the subcutaneous model, and 77d ( 177 Lu-PSMA-617) and 61d (control) in the systemic model. Following treatment with AMG 160, 2/10 mice with subcutaneous and 7/9 mice with systemic tumors had not progressed at the end of the observation period (>100 days). In contrast, all mice in the 177 Lu-PSMA-617 and control groups succumbed to progressive disease. Conclusions: Our study demonstrates potent antitumor activity of AMG 160 monotherapy in models of metastatic CRPC that are resistant to PSMA-targeted radioligand therapy with 177 Lu-PSMA-617. These data provide a rationale for evaluating AMG 160 in patients with mCRPC who have progressed on 177 Lu-PSMA-617. AMG 160 is currently being evaluated in a phase 1 study in patients with mCRPC (NCT03792841 ). Acknowledgements: The authors would like to acknowledge Micah Robinson, PhD of Amgen Inc. for medical writing support and Hosein Kouros-Mehr, MD, PhD of Amgen Inc. for facilitating the collaboration and helpful discussions. Trial Registration: ClinicalTrials. gov Identifier: NCT03792841 Ethics Approval: All animal experimental protocols were approved by the UCLA Animal Research Committee (# 2005-090).